Penanganan Terbaik Pada Kelebihan Kapasitas Lembaga Permasyarakatan Di Beberapa Negara - Turnip Mega Marta; Putra Kurnia, Mahendra; Erawaty, Rika (Jurnal Risalah Hukum, 2023)
This research is motivated by the fact that there are still many Correctional Institutions in several countries that experience overcapacity of residents caused by the orientation of the application of imprisonment. This normative research aims to find out the best form of handling related to the overcapacity of prisons in several countries and whether the best treatment in several countries can be applied in Indonesia to reduce the overcapacity of prisons in Indonesia. The research method used in this research is doctrinal law research. The results found from this study indicate that the increase in the overcapacity of prisons in several countries is due to the practice of imprisonment. Therefore, it is necessary to develop and increase the effectiveness of alternative criminals, and it is necessary to reform the criminal law legislation for certain types of crimes.